2021
DOI: 10.1038/s41598-021-99231-x
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt/β-catenin signaling pathway has a healing ability for periapical periodontitis

Abstract: Various disease-related genes have recently been identified using single nucleotide polymorphisms (SNPs). This study identified disease-related genes by analyzing SNP using genomic DNA isolated from Japanese patients with periapical periodontitis. Results showed that the SNP in LRP5 demonstrated a significant genotypic association with periapical lesions (Fisher’s exact test, P < 0.05). We constructed an in vivo murine periapical periodontitis model to confirm the Wnt/β-catenin signaling pathway’s role in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Wnt signaling is a vital regulatory pathway in osteoblast differentiation . The regulation of Wnt/b-catenin signaling pathway inhibitors intensifies periapical lesions (Naruse et al, 2021). The effect of Wnt3a treatment on osteogenic function is temporally dichotomous (Tang et al, 2014).…”
Section: Wnt/b-catenin Signalingmentioning
confidence: 99%
“…Wnt signaling is a vital regulatory pathway in osteoblast differentiation . The regulation of Wnt/b-catenin signaling pathway inhibitors intensifies periapical lesions (Naruse et al, 2021). The effect of Wnt3a treatment on osteogenic function is temporally dichotomous (Tang et al, 2014).…”
Section: Wnt/b-catenin Signalingmentioning
confidence: 99%
“…To clarify the Wnt/ β-catenin pathway's role in the development of periapical periodontitis, we performed the root canal treatment on mice with induced periapical periodontitis in our previous study. The results of our in vivo experiments demonstrated that the application of LiCl into root canals accelerated the healing of periapical periodontitis 10 . Thus, these results imply that lithium ion (Li + ) diffused from LiCl has the healing ability for periapical periodontitis.…”
Section: Introductionmentioning
confidence: 58%
“…Our recent work demonstrated that the A1330V variant of LRP5 was associated with the development of periapical periodontitis 10 . According to the results of the SNP analysis, we speculated that the Wnt/βcatenin signaling pathway was associated with periapical periodontitis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…10 A recent study on periapical cementum demonstrated that administration of the Wnt/β-catenin inhibitor enlarged the periapical lesion, while applying lithium chloride to root canals accelerated periapical periodontitis healing. 46 These seemingly contradictory results can potentially be explained by the impact of the Wnt signaling on periodontal ligament and cementum in the inflammatory environment since both studies used a periodontal defect model. Several studies suggest that Wnt signaling may have an opposite regulatory effect on cementogenic differentiation and mineralization between PDLCs and cementoblasts/cementocytes.…”
Section: Discussionmentioning
confidence: 99%